2017
DOI: 10.7570/jomes.2017.26.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Obesity, Sarcopenia, and Osteoarthritis in the Elderly

Abstract: Background: The present study examined the correlations between obesity, sarcopenia, and osteoarthritis in Korea' s elderly population. Methods: A cross-sectional analysis of 1,865 and 1,769 respondents with knee osteoarthritis and lumbar spondylosis, respectively, was performed by using data from the 2010 and 2011 Korea National Health and Nutrition Examination Survey. Obesity was defined as a body mass index of ≥25 kg/m 2 ; osteoarthritis, as a Kellgren/Lawrence grade of ≥2; and sarcopenia, as an appendicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
0
29
1
2
Order By: Relevance
“…In addition, estradiol functions as an antagonist at the serotonin reuptake transporter by inhibiting serotonin reuptake transporter gene expression and increasing the actions of serotonin by lengthening the available time that it remains in synapses . For men, aging‐related decline of testosterone level might also cause metabolic imbalance leading to sarcopenic obesity, which in turn contributes to the risk of osteoarthritis . In addition, Ford et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, estradiol functions as an antagonist at the serotonin reuptake transporter by inhibiting serotonin reuptake transporter gene expression and increasing the actions of serotonin by lengthening the available time that it remains in synapses . For men, aging‐related decline of testosterone level might also cause metabolic imbalance leading to sarcopenic obesity, which in turn contributes to the risk of osteoarthritis . In addition, Ford et al .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 For men, aging-related decline of testosterone level might also cause metabolic imbalance leading to sarcopenic obesity, which in turn contributes to the risk of osteoarthritis. 21,22 In addition, Ford et al showed that low serum total testosterone has a positive association with incident depression in older men. 23 In this regard, middle-aged and older men and women who lack endogenous sex hormones might be vulnerable to both osteoarthritis and emotional disturbance through hormone-neurotransmitter interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study confirmed that exercise intervention proved to be safe and effective for reversing functional and cognitive decline among hospitalized older adults [118]. Concerning spinal sarcopenic patients with diabetes and obesity, studies recommend using the Rapid Geriatric Assessment tool and starting secondary prevention as soon as possible [119][120][121][122]. Overall, exercise training appears to ameliorate mitochondria-associated problems and improve spinal sarcopenia.…”
Section: Aerobic Trainingmentioning
confidence: 99%
“…Obesity may contribute to OA pathogenesis in two ways, by increasing joint load and mechanical wear of the joints, and by promoting systemic and local inflammation. Body composition studies demonstrated a direct association of obesity with the risk of knee OA, suggesting that weight loss strategies for knee OA should focus on reducing excess fat tissue [2,3]. Partial or full IFP resection has been used to reduce knee pain resulting from IFP inflammation and impingement during total knee arthroplasty [28].…”
Section: Adipokine Adiponectinmentioning
confidence: 99%
“…Obesity is a common metabolic syndrome caused by excess fat accumulation in the body due to disorders of fat metabolism. Previous research has demonstrated a strong association between knee OA and obesity [1][2][3][4][5]. Obesity not only causes increased weight bearing by the joint but also enhances adipokine production by the adipose tissue, thereby contributing to inflammatory or autoimmune diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%